1982
DOI: 10.1128/aem.43.6.1330-1334.1982
|View full text |Cite
|
Sign up to set email alerts
|

Multiplication of Legionella pneumophila in unsterilized tap water

Abstract: Naturally occurring Legionella pneumophila, an environmental isolate which had not been grown on artificial medium, was tested for the ability to multiply in tap water. A showerhead containing L. pneumophila and non-Legionellaceae bacteria was immersed in nonsterile tap water supplying this fixture. Also L. pneumophila and non-Legionellaceae bacteria were sedimented from tap water from a surgical intensive care unit. This bacterial suspension was inoculated into tap water from our laboratory. The legionellae i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 16 publications
2
61
0
1
Order By: Relevance
“…In Fig. 1 Legionella have been reported to exhibit brief periods of growth in both autoclaved drinking water [7], and in unsterilized drinking water [20]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Fig. 1 Legionella have been reported to exhibit brief periods of growth in both autoclaved drinking water [7], and in unsterilized drinking water [20]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The association of L. pneumophila with water and water systems is now well established [3,14,[20][21][22]. Because legionellae are ubiquitous in the natural environment, it is often difficult to 'track', the source of this organism.…”
Section: Discussionmentioning
confidence: 99%
“…The implication is that either (i) the presence of the small numbers of non-legionella organisms were not sufficient to provide the quantity of growth factors required or (ii) they were not provided by these microorganisms but were present in the natural tap water and were destroyed by autoclaving. Yee & Wadowsky (1982) also showed that L. pneumophila multiplied in non-sterile tap water in the presence of a stable population of other organisms in one of the waters tested but they made no conclusion about the possible association between the various bacterial populations.…”
Section: Discussionmentioning
confidence: 97%
“…This collapses to the regular beta-Poisson dose-response model. If we divide Equation (20) by Equation (21), we get the following function:…”
Section: Incorporation Of the Tdr Into Incubation Distributions Of Thmentioning
confidence: 99%
“…(18) L. pneumophila has been shown to survive and multiply in water at temperatures between 25°C and 45°C, with an optimal temperature range of 32-42°C. (20) Water delivery systems, including cooling towers, (21,22) whirlpools, (23)(24)(25) indoor fountains, (26) air conditioning, (27) and indoor plumbing, (19,(28)(29)(30) often operate within these ranges, providing ideal conditions for Legionella growth, and have been implicated in several outbreaks. (31) Transmission to human hosts occurs when contaminated water is aerosolized, and such water delivery systems often produce aerosols, which facilitate the spread of the pathogen, and deposit the pathogen into the respiratory airways.…”
Section: Introductionmentioning
confidence: 99%